Kumpulan Cerpen Lelaki Kantong Sperma Analisis Abnormalitas Seksual - Gita Galih Gumalang, A.A Gede; Banda, Maria Matildis (Humanis; Vol 25 No 3 (2021), 2021)
This article discusses the form of sexual abnormality from the short stories collection Lelaki Kantong Sperma by Putu Juli Sastrawan. This collection of short stories contains nine short stories, of which six short stories contain elements of sexual abnormalities. The focus of this research is on two things, namely to reveal the structure and the form of sexual abnormalities in the short stories collection of Lelaki Kantong Sperma. The analysis technique used in this research is purposive sampling technique. The method used to collect data is the literature study method. Description method is used to analyze data. The analysis of the six short story titles used structural theory from Burhan Nurgiyantoro's formulation and the theory of sexual abnormalities from Kartini Kartono. Based on the results of the analysis, it was found that the structure was formed of three elements, namely, groove, characterization, and background. Furthermore, the form of sexual abnormalities is clearly depicted, one of which is the character Setia in the short story “Menggiring Belia” who is sexually attracted to minors. Through this, it was revealed that the character Setia had a form of pedophile sexual abnormality.